Practical Methods to Improve Client Compliance in General Medicine - Luis Turabian, Jose (International Journal of General Practice, 2020)
There is a gap between theoretical knowledge about strategies and the techniques or methods to apply in the practice of the consultation to improve compliance. Within the framework of these strategies, a number of techniques to be used in certain situations can be cited: 1) Assessing readiness to change, importance and confidence; 2) Instruments for decision support; 3) Technique of the "pros and cons"; 4) Auto-monitoring techniques; 5) Technique of "information exchange"; 6) Feedback technique; 7) Brainstorming; 8) The “typical day”; and 9) Practical reminder systems for taking medication. A certain technique is not a universal procedure, but it is usually refined by trial and error, based on past experiences, and their choice and design are the responsibility of the general practitioner.
Keywords: Physician-Patient Communication; Adherence; Therapeutic Alliance; Motivational Interviewing; General Practice; Framework